Sociodemographic determinants of knowledge on HPV vaccination among Iranian women living in Malaysia - Minhat, Halimatus Sakdiah; Mustafa, J.; Sarabi, S. (IDOSI Publications, 2013)
Cervical cancer is one of the commonest cancers among women worldwide. This study aims to determine the level of knowledge related to Human Papilloma Virus vaccination (HPV) as a screening tool for cervical cancer and its sociodemographic determinants among Iranian women who are living in Malaysia. A cross-sectional study, using a convenience sampling method was conducted among 271 Iranian women aged 18 to 60 year olds who were living in Malaysia. Data collection was conducted using a self-administered questionnaire. A total of 271 Iranian women had participated in this study, with the mean age of 35.2 years. Majority of the respondents involved were 30 years of age and above (57.9%), single (51.7%), received tertiary education level (82.7%), unemployed (68.6%) and had no income (68.3%), did not have any children (57.9%) and also had poor knowledge on HPV vaccination (84.5%). The mean score for knowledge among the respondents was 2.258. Although all the sociodemographic factors studied had significant association with the level of knowledge on HPV vaccination (p<0.05), but only marital status was found to be the only significant predicting factor for knowledge on HPV vaccination in the final predictive model obtained. Overall, the Iranian women who participated in this study had poor knowledge regarding HPV vaccination reflecting the needs for targeting the foreign residents living in Malaysia in any health promotion and education programme. This includes the use of a more understandable way of delivering the message such as the use of English language in the posters and mass media instead of only local language. The results are helpful in benchmarking the HPV related knowledge among the Iranian Immigrants and could be used in the development of appropriate educational messages for the future cohort.